Pattern Of Ocular Morbidity in School Children in Central India - Singh, Harpal (National Journal of Community Medicine, 2011)
School eye health services is one of the important aspect of school health services in which children can be screened for various systemic and eye diseases such as refractive error, squint, amblyopia, cataract, vitamin deficiency etc . The basic aim of this study was to assess the prevalence and pattern of visual impairment amongst school children of central India and to recognize avoidable causes of ocular morbidity. School surveys were conducted in various government schools of rural, urban and semi urban areas of Bhopal between Nov-2004 to Dec-07. A total of 20,800 school children between age group 5 to 16 years had under gone the complete ocular examination. Prevalence of Ocular morbidity was found in 14.5%. Refractive error was found to be the most common cause of ocular morbidity (47.91%) followed by vitamin A deficiency (13.66%) and strabismus (2.08%).